2002
DOI: 10.1111/1468-5957.00447
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of LBOs on the Performance of Acquired Firms: The French Case

Abstract: This paper investigates the financial characteristics and changes in performance of French companies involved in a leveraged buy-out. The empirical study covers a sample of 161 MBOs in France from 1988 to 1994. The acquired firms outperform their counterparts in the same sector of activity before and after the buy-out. However, unlike findings concerning LBOs in the USA and the UK, the performance of French firms falls after the operation is completed. This downturn in performance seems to be less detrimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 33 publications
5
54
1
Order By: Relevance
“…In addition, the studies are mainly concentrated on analysis of the US and UK markets. One notable exception is the study by Desbrières and Schatt (2002), who investigate the French market. In a study of 161 management buyouts during 1988−1994 the authors claim that firms acquired tend to outperform their non-acquired counterparts both before and after the buyout.…”
Section: Literature Review On Performance Studies: the Impact Of Actimentioning
confidence: 99%
“…In addition, the studies are mainly concentrated on analysis of the US and UK markets. One notable exception is the study by Desbrières and Schatt (2002), who investigate the French market. In a study of 161 management buyouts during 1988−1994 the authors claim that firms acquired tend to outperform their non-acquired counterparts both before and after the buyout.…”
Section: Literature Review On Performance Studies: the Impact Of Actimentioning
confidence: 99%
“…There is evidence that MBOs result in increased debt, Kaplan (1989a), Opler (1993) and Desbrieres and Schatt (2002 (2008) found that in the UK firms going private had lower debt ratios than firms remaining public.…”
Section: Leveragementioning
confidence: 99%
“…The regression adjusted entries are based on the estimates from columns (3) and (4) of Table 3. Kaplan (1989a) 20% increase in operating income/assets, and >28% increase in net cash flow/sales Lichtenberg and Siegel (1990) 6% increase in TFP Muscarella and Vetsuypens (1990) Increase in operating income/assets Smith (1990) 3-6% increase in operating income/assets Wright et al (1992) Significant increase in profit Wright et al (1997) 1-3% increase in ROA Desbrieres and Schatt (2002) Decrease in operating income/assets Harris et al (2005) >70% increase in TFP Cressy et al (2007) 5% increase in ROA Vinten (2007) 4% decrease in ROA Guo, Hotchkiss, and Song (2008) 12% increase in EBITDA/sales Meuleman et al (2008) Insignificant change in ROCE Weir, Jones, and Wright (2008) Mixed evidence on ROCE, and insignificant change in ROE TFP: total factor productivity. ROA: return on assets.…”
Section: Resultsmentioning
confidence: 99%